Program Pendampingan Penguasaan Cetak Massal untuk Pengembangan Industri Kreatif Rencong Souvenir - Husni, Husni; Putra, T. Edisah; Husaini; Arhami; Masri, Masri; Machmud, M. Nizar; M Nural Fajri (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aims to increase the production capacity of the creative rencong souvenir industry through mentoring in mastering mass printing technology. The rencong, as a traditional Acehnese weapon, has been transformed into a souvenir product with significant economic potential, yet it remains constrained by the limitations of conventional production techniques. Through this program, craftsmen and small and medium enterprises (SMEs) in the rencong souvenir sector receive intensive training and mentoring on efficient and high-quality mass printing techniques. The methods employed include technology transfer, hands-on training, and continuous monitoring to ensure program sustainability. The expected outcomes are improved productivity, production efficiency, and product quality standardization, ultimately enhancing the competitiveness of the creative rencong souvenir industry in both local and national markets. This program is also designed to positively impact local economic empowerment while preserving Aceh's cultural heritage through innovative creative industry products.